2008
DOI: 10.1155/2008/782381
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Kidney Cancer

Abstract: Some tumors are known to have a definite cause-effect etiology, but renal cell carcinoma (RCC) is not one of them precisely. With regard to RCC we can only try to identify some clinical and occupational factors as well as substances related to tumorigenesis. Smoking, chemical carcinogens like asbestos or organic solvents are some of these factors that increase the risk of the RCC. Viral infections and radiation therapy have also been described as risk factors. Some drugs can increase the incidence of RCC as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 52 publications
4
40
0
2
Order By: Relevance
“…The incidence of RCC peaks in the sixth decade of life and 80% of cases occur between the ages of 40 and 69 (9). Consistent with literature, the mean age of our patients was 54.9 years.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of RCC peaks in the sixth decade of life and 80% of cases occur between the ages of 40 and 69 (9). Consistent with literature, the mean age of our patients was 54.9 years.…”
Section: Discussionsupporting
confidence: 89%
“…Some of the vital risk factors influencing renal cell carcinoma (occurs in renal cortex) includes diet, obesity, lifestyle and habits (Pascual and Borque, 2008). A case-control study performed in 2007-2010 with patients of kidney cancer revealed that drinking water containing arsenic (in a dose dependent manner) may cause renal pelvis and ureter cancer (Ferreccio et al, 2013a).…”
Section: Bladder and Kidneymentioning
confidence: 99%
“…4,5,7,8 80% of RCCs are diagnosed in patients aged between 40 and 69 years with an average age in the low 60s. 9,10 Worldwide, the incidence of total kidney cancer and simultaneously RCC has steadily increased over the last 2 decades, while the mortality has decreased. 5,8,9,[11][12][13] This rise in incidence appears to result from an increase in the frequency of risk factors such as obesity and smoking and in the more frequent usage of diagnostic imaging procedures.…”
Section: Introductionmentioning
confidence: 99%